The evaluation of bulbar dysfunction in amyotrophic lateral sclerosis: survey of clinical practice patterns in the United States. Issue 5 (3rd July 2017) - Plowman, Emily K.; Tabor, Lauren C.; Wymer, James; Pattee, Gary
Abstract: Objective : Speech and swallowing impairments are highly prevalent in individuals with amyotrophic lateral sclerosis (ALS) and contribute to reduced quality of life, malnutrition, aspiration, pneumonia and death. Established practice parameters for bulbar dysfunction in ALS do not currently exist. The aim of this study was to identify current practice patterns for the evaluation of speech and swallowing function within participating Northeast ALS clinics in the United States. Methods and results : A 15-item survey was emailed to all registered NEALS centres. Thirty-eight sites completed the survey. The majority (92%) offered Speech-Language Pathology, augmentative and alternative communication (71%), and dietician (92%) health care services. The ALS Functional Rating Scale-Revised and body weight represented the only parameters routinely collected in greater then 90% of responding sites. Referral for modified barium swallow study was routinely utilised in only 27% of sites and the use of percutaneous gastrostomy tubes in ALS patient care was found to vary considerably. Conclusions : This survey reveals significant variability and inconsistency in the management of bulbar dysfunction in ALS across NEALS sites. We conclude that a great need exists for the development of bulbar practice guidelines in ALS clinical care to accurately detect and monitor bulbar dysfunction.